Explanatory domain and indicator for integration public skill training institute with private training center for automotive industry trainees explanatory domain and indicator for integration public skill training Institute with private training center for automotive industry trainees - Abd Samad, Noorazman; Wan Ahmad, Wan Mohd Rashid; Lai, Cee Sern; Harun, Hairuddin; Awang, Halizah; Ismail, Affero (American Scientific Publishers, 2017)
The Delphi technique was used to explore the domain and indicators that contribute towards the integration program Public Skills Training Institute (PSTI) and Private Training Centre (PTC) for automotive industry trainess. Domain analysis and indicators of the fourth round of the eleven (n=11) expert panel found that only twelve domain PSTI programmes are integrated with PTC namely (1) Governance; (2) The framework of qualifications; (3) Standard of competence; (4) Supplier of skill standards; (5) Delivery; (6); (7) industrial relations; (8) The experience of industrial work; (9) The twinning program; (10) community service program; (11) The curriculum-based industrial visits; and (12) Educational entrepreneurship. The contribution of this reserach is significant to realized by stake holders to strengthen the impelmentation of TVET training syatem in the country. In conclusion, this study is important to support PSTI, PTC and industry is to produce of skilled workers with high incomes and the desires to become a develop nation by 2020.